Prevalence of drug abuse among youth in Mubende Regional Referral Hospital. A cross-sectional study. - Kazini, James; Okadapaoo Imwangan, Alois; Nansereko, Hasifah; Ssemuwemba, Franscisco; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background: Understanding the prevalence of drug abuse among youth is essential for assessing the magnitude of the problem and guiding appropriate public health interventions. Therefore, this study aims to determine the prevalence of Drug Abuse among Youth in Mubende Regional Referral Hospital. Methodology: The study adopted a cross-sectional study design in which quantitative data were collected. Questionnaires were used to collect data from 54 respondents. Data was analyzed using Microsoft Excel, and results were generated and presented in tables, charts, and graphs. Results: Most of respondents 33(61.1%) were aged 20-25 years whereas 21(38.39) were aged 15-19 years. Majority of the respondents 42(77.78%) were male while 12(22.22%) were female. Most of them, 25(46.3%), had attained primary education, whereas the least, 7(12.96%), had attained tertiary education. A significant number of youths, 44(81.48%), were Christians. The leading source of income was business 21(38.89%), and the least 13(24.07%) reported salary as their main source of income. 50(94%) reported having used a drug at a point in their life, whereas 4(6%) reported not having used a drug. Alcohol was the most commonly abuse drug 34(62.96%), following by khat 9(16.67%), then marijuana 5(9.26%), and the least abused was aviation oil 3(5.56%) and kuber 3(5.56%). 36(66.67%), started using drugs between 13 and 15 years, whereas the least number, 4(7.41%), started using drugs above 15 years. 42(77.78%), reported daily drug use, whereas the least4(7.41%) reported using drugs once a month. Conclusion: Drug abuse is a significant concern among youth, highlighting the need for focused public health and clinical interventions. Recommendation: Implement routine screening and targeted prevention programs to reduce substance use and its associated risks.